The New Natural Distribution Area of Aspen (Populus tremula L.) Marginal Populations in Pasinler in the Erzurum Province, Turkey, and its Stand Characteristics - Özel, Halil Barış; Ayan, Sezgin; Erpay, Serdar; Simovski, Bojan (Hrvatski Sumarski Institut (Croatian Forest Research), 2018)
Background and Purpose: Genetic diversity is the basis for adaptation and survival of tree species under changing environmental conditions, representing the key issue of stability and productivity of forest ecosystems. This paper studies the marginal population characteristics and stand dynamics of aspen tree (Populus tremula L.) in natural, pure and mixed forest stands with Scots pine (Pinus sylvestris L.). These populations were observed on founding sites between Timarli Valley and Timan Plateau located in Pasinler in the Erzurum Province in Turkey. Materials and Methods: Three replicated sample sites were established according to a randomised block design with a spacing of approximately 200 m in altitude starting from 1,890 m, which is the natural distribution area of P. tremula, up to 2,460 m, above which this species can no longer thrive. Timarlı Valley, Pasinler Erzurum Province, which is the area of research, is located enroute to Timan Plateau, where Scots pines form the alpine tree line ranging up to 2,680 m a.s.l. Results: In this context, aspen trees in this region are the second closest tree species to the tree line after Scots pine, which are found in the subalpine and war zones. In addition, as a result of this study, it has been found out that this species, notwithstanding its natural area of occupancy across Turkey, could thrive up to 2,460 m in altitude and extent of occurrence. Conclusions: A new marginal natural population related to aspen has been found in Pasinler in the Erzurum Province, Turkey, which at the same time indicates that the timberline value in the vertical natural distribution of these species should be updated. Aspen trees, which as pioneer trees play a vital role in the rebuilding or restoring of the ecological balance in forests that over time become degraded because of excessive cutting of trees and erroneous silvicultural interventions should be used in the reclamation of broadleaved and mixed forests in a planned manner. Genetic resources that represent marginal and peripheral populations, both within and outside the natural distribution area, should be established and protected.
Keywords: natural distribution; Marginal Population; elevation; stand characteristics; Scots Pine; Ecology and Evolutionary Biology; Plant Sciences; Aspen; marginal population; Agriculture; Genetics and Genomics; Forestry; SD1-669.5; Natural Distribution; Stand Characteristics; Elevation; Scots pine; Forest Sciences; 15. Life on land